THE ADDITION OF COCONUT WATER AND THIAMINE TOWARDS CHRYSSANTHENUM MICRO CUTTINGS (Dendranthema grandiflora Tzvelev) IN VITRO - Salma Nabila; Endah Budi Irawati; Rina Srilestari (Jurnal Agrivet, 2021)
Chryssanthenum is ornamental plant with variety of shape and color which are unique and appealing. So that, it is in great demand in the community. The production of Chrissanthenum conventionally hampered by availability and quality of seeds. Thus, it needs research through tissue culture. The aim of this research is to know interaction between coconut water and thiamine and to determine the best coconut water and thiamine concentration toward Chryssanthenum micro cuttings. This research used laboratory experimental method by using completely randomized design with two factor. The 1st factor was coconut water concentration consisted of three level which were 5%, 10% and 15%. The 2nd factor was thiamine concentration consisted of three level which were 1mg/L, 2 mg/L and 3 mg/L. From the two factors, those were found that, there were nine combination of treatments and repeated 3 times. The variety  of data was analyzed by using Analysis of Variance (ANOVA) with level of α=5%, and continued by examining Duncan’s Multiple Range Test (DMRT) with level of α=5%. The result indicated that the interaction of coconut water concentration was 5% and thiamine was 1 mg/L on the parameters when growing shoot. There was also interaction on coconut water concentration which was 10 % and thiamine was 1 mg/L on the parameters in the number of shoots. interaction of coconut water combination was 15% and thiamine was 2 mg/L on  fresh weight. The addition of 10% coconut water and 1 mg/L thiamine showed the best result on shoot length.